'Listen to that gramophone' – Part-talkie production at AB Svensk Filmindustri. Issue 2 (29th August 2012) - Natzén, Christopher
The film 'Konstgjorda Svensson'/'Artificial Svensson' (Edgren, 1929) has recently been restored with its original soundtrack by the Swedish Film Institute. The restoration shows how film production companies in Sweden tried to connect the new medium of sound film to other sound technologies like radio and gramophone. Using the case study of early sound film production at the company Svensk Filmindustri, this article examines how gramophonic recordings of music facilitated the assimilation of sound and dialogue within the diegesis, making for a smooth conversion to sound. A distinguishing feature during the first sound years was that dialogue and sound created a heightened media-sensitivity. Music that adheres more to the demands of the narrative than to the image per se facilitated this process, masking the technical construction of the film medium.